Conceptual processes involved in words and scenes context effect in face recognition. Issue 6 (3rd July 2019) - Vakil, Eli; Vardi-Shapiro, Noa
ABSTRACT: Several studies have established the impact of conceptually similar context on the emergence of "Context-Effect" (CE). None of these studies included the Re-pair/rearrange condition at the test, which prevented them from being conclusive about the exact process (binding/ensemble or familiarity) that was affected by the conceptually similar context. To this end, in the present study faces (target to be remembered) were presented in the context of either words (W) or picture (P) scenes, and at test Re-pair was added as one of the context conditions. At test two groups were presented with the same context as in study (consistent condition) (WW & PP), and two groups with the inconsistent condition (WP & PW). Results showed no familiarity effect when only the conceptual match was preserved (i.e., inconsistent condition) and both effects of binding and familiarity when both conceptual and perceptual match were present (i.e., consistent condition). Thus, the semantic association between a face and context could serve as recognition cues even when modality has been changed, but the label remained constant.